2008
DOI: 10.1016/j.jvs.2007.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Suprarenal endograft fixation and medium-term renal function: Systematic review and meta-analysis

Abstract: Currently available data are insufficient to determine the precise effect of suprarenal fixation on medium-term renal function. Conventional Kaplan-Meier analysis of the pooled data set suggested that suprarenal fixation increased the risk of renal dysfunction; however, the effect disappeared when sophisticated statistical modelling was performed to account for study heterogeneity. A randomised controlled trial of suprarenal fixation may resolve this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 46 publications
2
45
3
3
Order By: Relevance
“…A meta-analysis of these studies provided conflicting results according to the analytical method used and concluded that the data were insufficient to draw any strong conclusions on the impact of suprarenal fixation. 254 None of the studies assessing renal function after AAA repair has used multilevel modelling to calculate annual rates of change in eGFR, and most have used creatinine or creatinine clearance rather than eGFR so it is difficult to compare results directly with those presented in this report. However, all studies have concluded that the reasons for renal function deterioration are likely to be multifactorial.…”
Section: Renal Functionmentioning
confidence: 99%
“…A meta-analysis of these studies provided conflicting results according to the analytical method used and concluded that the data were insufficient to draw any strong conclusions on the impact of suprarenal fixation. 254 None of the studies assessing renal function after AAA repair has used multilevel modelling to calculate annual rates of change in eGFR, and most have used creatinine or creatinine clearance rather than eGFR so it is difficult to compare results directly with those presented in this report. However, all studies have concluded that the reasons for renal function deterioration are likely to be multifactorial.…”
Section: Renal Functionmentioning
confidence: 99%
“…The fifth meta-analysis was based on individual patient data from five comparative nonrandomized studies. Outcomes included all-cause mortality or major adverse clinical events in four meta-analyses and complication-free survival time free in one meta-analysis [30].…”
Section: Meta-analysesmentioning
confidence: 99%
“…In four meta-analyses, the analysis was fully Bayesian, whereas the main outcome in one was also assessed using standard statistical analyses [30]. In all meta-analyses, the reason for adopting Bayesian methods was dealing with heterogeneity among trials in the analysis based on hierarchical random-effects models.…”
Section: Meta-analysesmentioning
confidence: 99%
“…Renal function outcomes have been attributed to several risk factors, both modifiable and non-modifiable, which include contrast usage, length of procedure, age, microemboli, baseline renal dysfunction and ace-inhibitor use (13,14). However the effects of proximal fixation and seal, and suprarenal fixation stents versus infrarenal fixations stents, on renal function are unclear (14,15). Understanding, preventing, and reducing the individual patient's modifiable and nonmodifiable risk factors allow for the best renal outcomes following EVAR.…”
Section: Clinical Indications and Contraindicationsmentioning
confidence: 99%